Tuning the thermoelectric properties of A-site deficient SrTiO3 ceramics by vacancies and carrier concentration. Issue 38 (14th September 2016) - Srivastava, Deepanshu; Norman, Colin; Azough, Feridoon; Schäfer, Marion C.; Guilmeau, Emmanuel; Kepaptsoglou, Demie; Ramasse, Quentin M.; Nicotra, Giuseppe; Freer, Robert
Abstract : The work demonstrates the relative contributions to enhanced thermoelectric performance in perovskites from (i) vacancies and (ii) charge carriers. Abstract : Ceramics based on Sr0.8 La0.067 Ti0.8 Nb0.2 O3− δ have been prepared by the mixed oxide route. The La1/3 NbO3 component generates ∼13.4% A-site vacancies; this was fixed for all samples. Powders were sintered under air and reducing conditions at 1450 to 1700 K; products were of high density (>90% theoretical). Processing under reducing conditions led to the formation of a Ti1− x Nb x O2− y second phase, core–shell structures and oxygen deficiency. X-ray diffraction (XRD) confirmed a simple cubic structure with space group Pm 3̄ m. Transmission electron microscopy revealed a high density of dislocations while analytical scanning transmission electron microscopy at atomic resolution demonstrated a uniform distribution of La, Nb and vacancies in the lattice. X-ray photoemission spectroscopy and thermogravimetry showed the oxygen deficiency ( δ value) to be ∼0.08 in reduced samples with enhanced carrier concentrations ∼2 × 10 21 cm −3 . Both carrier concentration and carrier mobility increased with sintering time, giving a maximum figure of merit ( ZT ) of 0.25. Selective additional doping by La or Nb, with no additional A site vacancies, led to the creation of additional carriers and reduced electrical resistivity. Together these led to enhanced ZT values of 0.345 at 1000 K. The contributions from oxygen vacancies and charge carriers have been investigated independently.